Studi Penggunaan Abu Cangkang Kenari Sebagai Subtitusi Bahan Pengisi (Filler) Pada Campuran HRS-WC Terhadap Stabilitas Marshal - Fuad Hasan Ohorella; Juliet G. Metekohy; Asri K. Patty (Jurnal Teknik Sipil Unaya, 2023)
The flexible pavement generally used in Indonesia is Thin Asphalt Concrete (HRS). The layer that receives the greatest traffic load is the wear layer (HRS-WC). One of the ingredients for the pavement layer is filler. To overcome the adequacy of filler, cement or lime is used, because the use of fillers is generally very expensive. Therefore, it is necessary to innovate the development of alternative fillers. This study aims to obtain the Marshall stability value of the HRS-WC mixture using walnut shell ash filler. The method used is an experimental study method on the technical specifications of the Directorate General of Highways 2018. The test results obtained optimum asphalt content (KAO) of 7.25% using a variation of cement filler mixture 2% : 0% walnut shell ash to obtain a stability value of 1892.16 kg, for filler 2% : 1% of 1714.90 kg, for filler 1% : 2% is 1877.45 kg and for filler 0% : 3% is 1989.96 kg. Where filler cement 0% : 3% walnut shell ash has the greatest recovery value of each variation of the filler tested. Overall, the use of walnut shell ash as an alternative filler can be utilized in asphalt pavement mixtures.